DNA tumour viruses : virology, pathogenesis and vaccines - Roberts, Sally (Senior lecturer in Cancer Studies) (Caister Academic Press, 2018)
In this timely book, expert authors review the most important current research in this rapidly growing field. Topics covered range from an overview of the contribution of DNA tumour viruses to the cancer burden worldwide, and the molecular pathogenesis of virus driven cancers to vaccine development. This volume will serve as a valuable reference source for everyone working in the field, both experts and students, in academia, government, and biotechnology companies. It is also a must-read for anyone with an interest in viral tumourigenesis and an important acquisition for all microbiology libr.